2013
DOI: 10.1167/iovs.12-10602
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of T-Lymphocyte CCL3 and CCL4 Production by Retinal Pigment Epithelial Cells

Abstract: PURPOSE.Retinal pigment epithelial (RPE) cells have an important role in the immune suppression associated with the immune privilege of the eye. Some aspects of this remain unclear and this study aimed to determine how RPE cells could influence the production of chemokines by T lymphocytes.METHODS. T lymphocytes, separated from peripheral blood of normal volunteers, and RPE cells, cultured from donor eyes, were cultured separately and together, either in contact or in transwells. Supernatants were analyzed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…RPEconditioned medium can differentiate naive T cells to regulatory T (T reg ) cells (61,62). Cocultured RPE can suppress T-cell activation (11) by producing both soluble and membrane-associated immunomodulatory factors (63)(64)(65)(66). Results from our current study show that the ex vivo coculture of RPE with splenic gd T cells directed the differentiation toward regulatory gd T cells that produced suppressive cytokines, such as IL-4 and IL-10 (Fig.…”
Section: Discussionmentioning
confidence: 69%
“…RPEconditioned medium can differentiate naive T cells to regulatory T (T reg ) cells (61,62). Cocultured RPE can suppress T-cell activation (11) by producing both soluble and membrane-associated immunomodulatory factors (63)(64)(65)(66). Results from our current study show that the ex vivo coculture of RPE with splenic gd T cells directed the differentiation toward regulatory gd T cells that produced suppressive cytokines, such as IL-4 and IL-10 (Fig.…”
Section: Discussionmentioning
confidence: 69%
“…It was previously reported that PGE2 mediated the regulatory function of RPE cells in inflammatory T cells through downregulated CCL4. 39 Moreover, the COX2-PGE2 pathways also contribute to the immunoregulatory function of MSCs or regulatory macrophages in modulating other inflammatory diseases. 37,38 On the other hand, however, PGE2 and COX2 were thought to be the The ARPE19 cells were stimulated with different doses of A2E (0, 2, 10, 25 lM) for 6 hours.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] To investigate the mechanisms involved in RPE immunosuppression function in our system, we analyzed PGE2 and COX2 expression in RPE cells by ELISA and Western blot. We found that A2E reduced PGE2 level in RPE cells compared with RPE cells without stimulation (P < 0.01).…”
Section: The A2e Reduced Immunosuppressive Function Of Rpe Cells Thromentioning
confidence: 99%
“…SB431542, which was used to inhibit TGF-β signaling, did not completely block the inhibition of T-cell activation by iPSC-RGCs. In human RPEs, some factors other than TGF-β, such as prostaglandin E2 and soluble CD54, have also been reported to be involved in suppression of T-cell activity [3]. Thus, TGF-β mainly contributes to the T-cell suppression by iPSC-RGCs, but other immunosuppressive molecules other than TGF-β may also contribute.…”
Section: Discussionmentioning
confidence: 99%
“…Retinal ganglion cells (RGCs), which are located in the innermost layer of the retina, are responsible for collecting optical information that reaches the retina, and transmitting it to the brain via the optic nerve [ 1 ]. Retinal pigment epithelial cells (RPEs), which are one of the constituent cells of the retina as well as RGCs, have been reported to possess immune-suppression capacity [ 2 , 3 , 4 , 5 , 6 ]. Stem cell-derived RPE transplantation therapy has already been applied clinically [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%